The Effectiveness of Digital Literacy on Student Science Learning Outcomes during the Covid-19 Pandemic - Akhyar, Yundri; Fitri, Anggi; Zalisman, Zalisman; Syarif, Muhammad Ilham; Niswah, Niswah; Simbolon, Parlindungan; Purnamasari S, Ayu; Tryana, Nofita; Abidin, Zaitun; Abidin, Zaitun (International Journal of Elementary Education, 2021)
Online learning has a negative impact on students who cannot use online learning support facilities, of course this has an impact on reducing learning outcomes. This study aims to analyze the effect of implementing digital literacy on students' science learning outcomes during the COVID-19 pandemic. The type of research used is correlation. The population of this study was 348 people. Data collection methods used were questionnaires and science learning outcomes tests that had been tested for validity and homogeneity. The data analysis used is simple linear regression, but previously a prerequisite test was carried out. The results showed the calculation of the correlation coefficient of 4.412 is greater than 2.034 with a significance value of 0.000 smaller than the alpha value of 0.05, the coefficient of determination of 0.371 x 100% of 37.1%. So, there is a positive and significant effect of the application of digital literacy on students' science learning outcomes.